Efficient strategy for the construction of both enantiomers of the octahydropyrroloquinolinone ring system: total synthesis of (+)-aspidospermidine - Pandey, Ganesh; Burugu, Shiva Kumar; Singh, Pushpendra (Organic Letters, 2016)
An efficient and highly stereoselective intramolecular [3 + 2] cycloaddition of nonstabilized azomethine ylide generated from a designed bicyclic aminal precursor is reported for the synthesis of both (-)- and (+)-octahy-dropyrroloquinolinone. One of the enantiomers is further advanced to accomplish the total synthesis of (+)-aspidospermidine.